1990
DOI: 10.1063/1.344663
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the electrical resistivity in the magnetic Kondo lattice systems CePtGe and CePt2

Abstract: Articles you may be interested inDependence of the intrinsic dTc/dp of YBa2Cu3Ox on the oxygen content and the additive Tc increase by pressureinduced oxygen ordering AIP Conf. Proc. 309, 703 (1994); 10.1063/1.46430High pressure studies on the ferromagnetic dense Kondo systems CeRh3B2 and UCu2Ge2 AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Fig. 3(a) displays the resistivity q(T) of Ce 1Àx Pb x Pt 2 in the temperature range 0.35 6 T 6 300 K. The metallic behavior for x = 0 is consistent with the previously reported one [9]. The room-tem- perature value for x = 0.27 is twice as large as that for x = 0.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Fig. 3(a) displays the resistivity q(T) of Ce 1Àx Pb x Pt 2 in the temperature range 0.35 6 T 6 300 K. The metallic behavior for x = 0 is consistent with the previously reported one [9]. The room-tem- perature value for x = 0.27 is twice as large as that for x = 0.…”
Section: Resultssupporting
confidence: 86%
“…Because T K is comparable with T N , CePt 2 was expected to be suitable for the investigation of the quantum critical behavior under pressure. However, no significant change in T N was observed in the applied pressure up to 2 GPa [9]. In contrast, T N was found to be depressed by substituting Rh and Ir for Pt in CePt 2 [10].…”
Section: Introductionmentioning
confidence: 52%
“…It has been observed that TN is not very sensitive to pressure in this compound [478]. CePtGe shows an increase in resistivity at ambient pressure on cooling from room temperature and shows a broad peak around 150 K, which deceases steeply down to 15 K and resumes a step drop at 10 K [478]. Such a double peak structure of resistivity suggests the Kondo behavior in this compound as seen in many compounds mentioned earlier.…”
Section: Magneto-transport Propertiesmentioning
confidence: 75%
“…The resistivity in CePtGe does not show any change at high temperatures on the application of pressure, however at low temperatures the shoulder accentuates on increasing pressure upto the highest pressure of 17.4 kbar [478]. It has been observed that TN is not very sensitive to pressure in this compound [478]. CePtGe shows an increase in resistivity at ambient pressure on cooling from room temperature and shows a broad peak around 150 K, which deceases steeply down to 15 K and resumes a step drop at 10 K [478].…”
Section: Magneto-transport Propertiesmentioning
confidence: 99%
See 1 more Smart Citation